A Möbius Aromatic [28]Hexaphyrin Bearing a Diethylamine Group: A Rigid but Smooth Conjugation Circuit1. (4th February 2015) - Higashino, Tomohiro; Soya, Takanori; Kim, Woojae; Kim, Dongho; Osuka, Atsuhiro
Abstract The reaction of [26]hexaphyrin with triethylamine in the presence of BF3⋅OEt2 and O2 furnished a diastereomeric mixture of a diethylamine‐bearing [28]hexaphyrin as a rare example of a Möbius aromatic metal‐free expanded porphyrin. The Möbius aromaticity of these molecules is large, as indicated by their large diatropic ring currents, which are even preserved at 100 °C, owing to their internally multiply bridged robust structure with a smooth conjugation network. These molecules were reduced with NaBH4 to give an antiaromatic [28]hexaphyrin, and were oxidized with MnO2 to give aromatic [26]hexaphyrins, both through a Möbius‐to‐Hückel topology switch induced by a CN bond cleavage.